Leveraging protected areas for dual goals of biodiversity conservation and zoonotic risk reduction - Li Yang (13558573) (2025)
Abstract Protected areas (PAs) are essential for biodiversity conservation, but their potential to reduce zoonotic risk remains underexplored. We analyzed 33,831 vertebrate species to identify high conservation need (HCN) and high zoonotic risk (HZR) areas. On average, 46% of HZR areas overlapped with HCN areas, highlighting potential alignment between conservation and risk reduction. Focusing on four vertebrate groups, we defined key HCN-HZR areas covering only 7 - 9% of global HCNs (~1% of land), offering cost-effective opportunities. These areas are located across 30 priority countries, containing 92% of global key HCN-HZR areas, yet average PA coverage was only 23%. Managing key HCN-HZR areas would require 6,500 - 45,000 additional rangers and $390 - $1,822 million annually. Encouragingly, allocating just 0.01% of national GDP would close most funding gaps. Expanding PA coverage and enhancing zoonotic surveillance in these critical areas could address both biodiversity loss and public health risk, particularly in underfunded countries. Highlights: 1. Expanding PAs in key HCN-HZR areas can reduce both biodiversity loss and zoonotic risk. 2. Thirty priority countries hold 92% of global key HCN-HZR areas. 3. PA management needs 6,500 - 45,000 rangers, costing $390 - $1,822 million annually. 4. Only 0.01% of national GDP in these countries could fill most of the investment requirement. Data Description 1. Code: The analysis is divided into two main parts: Part 1 (Step1_Spatial analysis.Rmd): Processes zonation maps to identify HCN and HZR areas, overlays them to derive HCN-HZR areas, and calculates distributions across taxonomic groups, protected areas, and countries. Part 2 (Step2_Spatial analysis.Rmd): Analyzes range sizes, PA coverage for HCN, HCN-HZR, and key HCN-HZR areas; estimates ranger needs and costs; performs sensitivity analyses; and generates supplementary tables. 2. Zonation Results Zonation analysis was conducted for four vertebrate groups (Amphibia, Aves, Mammalia, Reptilia) using CAZ and ABF algorithms under four settings. The analysis was performed at standard and lower (~10 km) resolutions. Processed zonation layers (thresholded at top 10%) are stored in ./3Spatial_result/1zonation_layer_LZW/. (after you run the code) Settings for Zonation Analysis Taxonomic Groups: Amphibia, Aves, Mammalia, Reptilia. Algorithms: Core Area Zonation (CAZ) and Additive Benefit Function (ABF). The following table summarizes the four settings used in the sensitivity analysis, following Nava-Bolaños et al. (2023): Neural Control: Assigned a weight of 1, this setting prioritizes areas based solely on species richness and does not consider human impact. Human Impact Control: Also assigned a weight of 1, this setting emphasizes areas with higher human disturbance, factoring in human impact. Extinction Risk: Weighted according to extinction risk, this setting prioritizes High Conservation Need (HCN) areas based on extinction risk weights and does not account for human impact. Zoonotic Risk: Weighted according to zoonotic risk, this setting prioritizes High Zoonotic Risk (HZR) areas based on zoonotic risk weights and incorporates human impact considerations. HCN-HZR Overlays: Derived HCN-HZR areas by overlaying HCN and HZR layers; key HCN-HZR areas require overlap across all four groups. Layers are in ./3Spatial_result/2HCN_HZR/. 3. Other Related Layers Additional datasets used in the analysis include: Ranger Density: Country-level data on ranger presence (updated for Asia from Farhadinia et al., 2023). GDP: Gross Domestic Product data at the country level (from tradingeconomics.com). Protected Area (PA) Data: Information on protected areas at the country level (./2other_related_layer/PA_map.tif). Population Data: Population statistics at the country level (./2other_related_layer/Population_map.tif). Income Data: Income levels at the country level. Zonation Weight: Raw data used for generating Table S4 (species weights in Table S3). Country Map: ./2other_related_layer/country_map.tif for zonal statistics. Conservation Costs: Compiled from 305 records across 29 sources for comprehensive PA management estimates (Table S7). 4. Supplementary Tables The analysis generates several supplementary tables stored in ./3Spatial_result/5sp_tables/ (after you run the code): Table S1. Top 30 Countries with the largest key HCN-HZR Areas, their PA Coverage on key HCN-HZR Areas, and economic income level for each country. The global national and regional boundaries obtained from the National Catalogue Service for Geographic Information (http://www.webmap.cn) and GADM (the Database of Global Administrative Areas) (https://gadm.org). Table S2. Ranger and investment requirements to achieve comprehensive management in protected areas of priority countries under different scenarios. Table S3. Lists species with their conservation-need and zoonotic-risk weights. Extinction-risk weights are based on IUCN status: 1 = Least Concern, 2 = Near Threatened, 3 = Vulnerable, 4 = Endangered, and 5 = Critically Endangered, with Data-Deficient species assigned a weight of 3. Zoonotic-risk weights were assigned to 33,831 species based on pathogen types: 5 for species with multiple zoonotic pathogens, 4 for one zoonotic pathogen, 3 for multiple non-zoonotic pathogens, 2 for one non-zoonotic pathogen, and 0.1 for species with no recorded pathogens. Data from the Amphibian Disease Portal on non-zoonotic infections in 1,394 amphibians were also included. Table S4. Summary of Zonation outcomes showing coverage within the top 10% priority areas for the ranges of 33,831 vertebrate species under different prioritization settings: extinction risk (weights based on species’ extinction risk), zoonotic risk (weights based on zoonotic risk with a human footprint condition layer), neutral control (all weights = 1), and human impact control (all weights = 1 with a human footprint condition layer). Each approach was run using both the Additive Benefit Function (ABF) and Core-Area Zonation (CAZ) algorithms. Table S5. Comparison of species range coverage under different prioritization settings and algorithms using Wilcoxon tests. Effect sizes were interpreted as small (0.1–0.3), moderate (0.3–0.5), and large (≥0.5). Table S6. Comparison of priority areas identified under different prioritization settings and algorithms at source resolutions of 1 km and 10 km, assessed using Jaccard similarity. Table S7 Summary of estimated financial investments for comprehensive PA management Additionally, figure plotting data is in ./3Spatial_result/4fig_table/Fig_plot_dat.xlsx, and Rdata files (e.g., layer_cal.Rdata) contain computed tables for HCN-HZR distributions. 5. Appendix Tables This is the supplemental tables which are deposited at figshare Table S1 Top 30 Countries with the largest key HCN-HZR Areas, their PA Coverage on key HCN-HZR Areas, and economic income level for each country. The global national and regional boundaries obtained from the National Catalogue Service for Geographic Information (http://www.webmap.cn) and GADM (the Database of Global Administrative Areas) (https://gadm.org). Table S2 Ranger and investment requirements to achieve comprehensive management in protected areas of priority countries under different scenarios Table S3 Lists species with their conservation-need and zoonotic-risk weights. Extinction-risk weights are based on IUCN status: 1 = Least Concern, 2 = Near Threatened, 3 = Vulnerable, 4 = Endangered, and 5 = Critically Endangered, with Data-Deficient species assigned a weight of 3. Zoonotic-risk weights were assigned to 33,831 species based on pathogen types: 5 for species with multiple zoonotic pathogens, 4 for one zoonotic pathogen, 3 for multiple non-zoonotic pathogens, 2 for one non-zoonotic pathogen, and 0.1 for species with no recorded pathogens. Data from the Amphibian Disease Portal on non-zoonotic infections in 1,394 amphibians were also included. Table S4. Summary of Zonation outcomes showing coverage within the top 10% priority areas for the ranges of 33,831 vertebrate species under different prioritization settings: extinction risk (weights based on species’ extinction risk), zoonotic risk (weights based on zoonotic risk with a human footprint condition layer), neutral control (all weights = 1), and human impact control (all weights = 1 with a human footprint condition layer). Each approach was run using both the Additive Benefit Function (ABF) and Core-Area Zonation (CAZ) algorithms. Table S5. Comparison of species range coverage under different prioritization settings and algorithms using Wilcoxon tests. Effect sizes were interpreted as small (0.1–0.3), moderate (0.3–0.5), and large (≥0.5). Table S6. Comparison of priority areas identified under different prioritization settings and algorithms at source resolutions of 1 km and 10 km, assessed using Jaccard similarity. Table S7 Summary of estimated financial investments for comprehensive PA management.